Cummins, Inc. : debating a governmental relations office in China (A) - Bagley, Constance E., (SAGE Knowledge. Cases., 2008)
Steve Chapman surveyed the northeast part of the city from his 27th-floor office. Though the sky was cloudy, he could see for miles. Beijing was well on its way to its 2007 target of 245 "blue sky days," part of an ambitious effort to improve air quality. As Group Vice President -- Emerging Markets and Businesses for Cummins, Inc., Chapman knew that Cummins could continue its success as one of the largest producers of diesel engines for the China market only if it continued to meet China's increasingly strict and occasionally fragmented air quality standards. He wondered if the company could participate more actively in the development of China's regulatory policy, taking a higher profile after 20 years of a low-profile approach with the government. Cummins had come late to a lobbying office in Washington, D.C., but setting up the office in 2001 had provided a strong business asset. Perhaps it was time to establish a government relations function in China.